Morphological characteristics of maxilliped lobsters (Panulirus spp) in Aceh Jaya Waters, Aceh Province - Irfannur Irfannur; Yusrizal Akmal; Muliari Muliari; Mardiana Mardiana (Program Studi Akuakultur, Fakultas Pertanian, Universitas Almuslim, 2023)
The waters of Aceh Jaya are home to six distinct species of Panulirus spp lobsters, specifically Panulirus penicillatus, P. longipes, P. ornatus, P. polyphagus, P. versicolor, and P. homarus. The study was carried out in 2022 within the aquatic territory of Aceh Jaya Regency. The lobster fishermen at the research area employ gill nets as their fishing gear. The data collection approach involves doing direct field observations and performing identifications in the laboratory. The analysis of the data is then carried out using descriptive techniques. During lobster fishing operations, fishermen engage in a daily routine that involves setting and hauling the fishing gear once a day. This process lasts for 16 hours and includes lifting the catch onto land. Analysed data on the six species of lobster (Panulirus spp) taken by lobster fisherman, specifically Panulirus penicillatus, P. longipes, P. ornatus, P. polyphagus, P. versicolor, and P. homarus. All six varieties of lobster have different morphological characteristic based on the color and shape of the maxilliped.